Conformational dynamics of Ca2+-dependent responses in the polycystin-2 C-terminal tail - Yang, Yifei; Hodsdon, Michael E; Lolis, Elias J; Ehrlich, Barbara E (Biochemical journal, 2016)
PC2 (polycystin-2) forms a Ca(2+)-permeable channel in the cell membrane and its function is regulated by cytosolic Ca(2+) levels. Mutations in the C-terminal tail of human PC2 (HPC2 Cterm) lead to autosomal dominant polycystic kidney disease. The HPC2 Cterm protein contains a Ca(2+)-binding site responsible for channel gating and function. To provide the foundation for understanding how Ca(2+) regulates the channel through the HPC2 Cterm, we characterized Ca(2+) binding and its conformational and dynamic responses within the HPC2 Cterm. By examining hydrogen-deuterium (H-D) exchange profiles, we show that part of the coiled-coil domain in the HPC2 Cterm forms a stable helix bundle regardless of the presence of Ca(2+). The HPC2 L1EF construct contains the Ca(2+)-binding EF-hand and the N-terminal linker 1 region without the downstream coiled coil. We show that the linker stabilizes the Ca(2+)-bound conformation of the EF-hand, thus enhancing its Ca(2+)-binding affinity to the same level as the HPC2 Cterm. In comparison, the coiled coil is not required for the high-affinity binding. By comparing the conformational dynamics of the HPC2 Cterm and HPC2 L1EF with saturating Ca(2+), we show that the HPC2 Cterm and HPC2 L1EF share a similar increase in structural stability upon Ca(2+) binding. Nevertheless, they have different profiles of H-D exchange under non-saturating Ca(2+) conditions, implying their different conformational exchange between the Ca(2+)-bound and -unbound states. The present study, for the first time, provides a complete map of dynamic responses to Ca(2+)-binding within the full-length HPC2 Cterm. Our results suggest mechanisms for functional regulation of the PC2 channel and PC2's roles in the pathophysiology of polycystic kidney disease.